1988
DOI: 10.1111/j.1600-0447.1988.tb08557.x
|View full text |Cite
|
Sign up to set email alerts
|

Past and present strategies of research on the HPA‐axis in psychiatry.

Abstract: Hypercortisolism in depression has been extensively studied during the last three decades. The main hypothesis regarding origin and clinical relevance of this phenomenon, however, has changed significantly. Up to the mid-seventies hypercortisolism was conceived as consequence of stress modified by the degree of unconscious defense mechanisms in different forms of depressive or non-depressive psychiatric disorders. At the end of the seventies this point of view changed considerably. Hypercortisolism was regarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The lack of a close relationship between the postulated second-order latent factor representing the hypothalamic influence over time, and cortisol secretion at each experimental occasion, may be explained by the fact that there is some evidence that external situational factors (e.g., health status, daily events, etc.) are involved in the regulation of cortisol secretion (Berger et al, 1988). Furthermore, some researchers have suggested that interindividual differences may be related to the individual unconscious defense mechanisms that partly determine the degree of the HPA system's activation during stressful events (Knight et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a close relationship between the postulated second-order latent factor representing the hypothalamic influence over time, and cortisol secretion at each experimental occasion, may be explained by the fact that there is some evidence that external situational factors (e.g., health status, daily events, etc.) are involved in the regulation of cortisol secretion (Berger et al, 1988). Furthermore, some researchers have suggested that interindividual differences may be related to the individual unconscious defense mechanisms that partly determine the degree of the HPA system's activation during stressful events (Knight et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cortisol secretion is most likely to accompany psychological stress that involves a perceived lack of control or social-evaluative threat [13]. However, there is considerable inter-individual variability in HPA activation during physical or mental stimulation [14, 15]. Some factors that might account for this variability include acclimation/habituation [16], early life experiences [17], sex [18] and genetics [14].…”
mentioning
confidence: 99%